Understanding the markets - Loader, David (Operations management series (Securities Institute))
An analysis of the major securities, derivatives and money markets from an operations point of view, 'Understanding the Markets' takes the reader through the major features and characteristics of the markets and the products. The relationship between the trading and dealing functions and the operations functions is examined and the issues discussed.This book looks at the financial markets from the viewpoint of the person working in the operations functions that support the trading, dealing and investment processes, and as such is essential reading in order to fully understand the industry - an.